A pragmatic framework for local operationalisation of national-level biodiversity impact mitigation commitments - Thomas B. Atkins; Natalie E. Duffus; Amber J. Butler; Hannah C. Nicholas; Sophus O.S.E. zu Ermgassen; Prue Addison; E.J. Milner-Gulland (Environmental Science & Policy, 2025)

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Using conservation science to advance corporate biodiversity accountability - Prue F. E. Addison; Joseph W. Bull; E. J. Milner‐Gulland (Conservation Biology, 2019)
Biodiversity declines threaten the sustainability of global economies and societies. Acknowledging this, businesses are beginning to make commitments to account for and mitigate their influence on biodiversity and report this in sustainability reports. We assessed the top 100 of the 2016 Fortune 500 Global companies' (the Fortune 100) sustainability reports to gauge the current state of corporate biodiversity accountability. Almost half (49) of the Fortune 100 mentioned biodiversity in reports, and 31 made clear biodiversity commitments, of which only 5 were specific, measureable, and time bound. A variety of biodiversity‐related activities were disclosed (e.g., managing impacts, restoring biodiversity, and investing in biodiversity), but only 9 companies provided quantitative indicators to verify the magnitude of their activities (e.g., area of habitat restored). No companies reported quantitative biodiversity outcomes, making it difficult to determine whether business actions were of sufficient magnitude to address impacts and were achieving positive outcomes for nature. Conservation science can advance approaches to corporate biodiversity accountability by helping businesses make science‐based biodiversity commitments, develop meaningful indicators, and select more targeted activities to address business impacts. With the biodiversity policy super year of 2020 rapidly approaching, now is the time for conservation scientists to engage with and support businesses in playing a critical role in setting the new agenda for a sustainable future for the planet with biodiversity at its heart.

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)